Changing borders and identities in the Kelabit Highlands :anthropological reflections in growing up near an international border - Poline, Bala (Universiti Malaysia Sarawak, 2002)
The central topic of this book is the. International border between Indonesia and Malaysia and its changing and evolving significance to the people of the Kelabit Highlands. Playing upon the multiple meanings inherent in the notions of "boundaries" and "borders " and of the role they play in creating and mediating identities, the author relates the account of the international border to her own odyssey from a Kelabit Highlands childhood to becoming an anthropologist and university lecturer.